Weakness of will in Renaissance and Reformation thought - Saarinen, Risto (Oxford : Oxford University Press, 2011)
The question of why people act against their better judgment has always been prominent in philosophy. Risto Saarinen presents the first study of ideas about weakness of the will between 1350 and 1650. He shows how the understanding of human conduct and free will changed in this formative period between medieval times and modernity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Will -- Philosophy; Change (Psychology); Philosophy, Renaissance; Philosophy and religion; Reformation